Statements of Belief as Political Communication - Timothy Nugent (Australian Journal of Law & Religion)
There is increased interest in legislation that shields some forms of expression not only from the legislature but also from sanctions by powerful private institutions such as social media companies, professional associations, and employers. The Religious Discrimination Bill 2022 (Cth), if passed, would have prohibited ‘qualifying bodies’ from implementing conduct rules that restrict ‘statements of belief’ in their effects. Other provisions of the Bill implicitly provided some protection for ‘religious speech’ within the broader ambit of ‘religious belief or activity’. Using the Religious Discrimination Bill as an example, this paper examines laws that restrict private censure of speech with respect to the implied freedom of political communication. It is argued that laws that limit private censorship of political speech may place a burden upon political communication if they are not constructed in a manner that is ‘viewpoint neutral’. Such laws can thus only be valid if the criteria of ‘compatibility’ and ‘proportionality’ are met (as established in Lange and its progeny). The power imbalance between individuals and large private institutions may warrant limits on private censorship. However, such limits are best framed so as not to discriminate between viewpoints. Laws that protect the expression of particular ideas, such as those based in religious doctrine, must demonstrate a legitimate reason for differential treatment compared to other foundational beliefs.